Fitness cost and competitive ability of ryegrass susceptible and with multiple resistance to Glyphosate, Iodosulfuron-methyl, and Pyroxsulam. - HENCKES, J. R. (2019)
ABSTRACT - Ryegrass is an important weed in wheat cultivations due to the evolution of resistance to different mechanisms of action. This study aimed to compare the phenological development, fitness cost, and competitive ability between ryegrass biotypes susceptible and with multiple resistance to 5-enolpyruvylshikimate3-phosphate synthase (EPSPs) and acetolactate synthase (ALS) inhibiting herbicides. Fitness cost and phenological development were evaluated from biotypes grown in pots, and morphological growth variables were determined up to 140 days after emergence. Phenological development was evaluated with a fitness cost. Competitive ability was determined in a replacement-series experiment with proportions of resistant and susceptible ryegrass. The tested proportions were 100:0 (pure resistant ryegrass stand), 75:25, 50:50, 25:75, and 0:100% (pure susceptible ryegrass stand), where the number of tillers, height, leaf area, and shoot dry matter were evaluated at 50 days after emergence. The longer tillering period of resistant ryegrass was the main factor involved in the difference in phenological development between biotypes. The resistant biotype was superior to the susceptible regarding height, shoot dry matter, and absolute growth rate, while the susceptible biotype had a higher number of tillers and leaf area ratio. Thus, the resistant biotype had no fitness cost. For competitive ability, no difference was observed between biotypes in the different tested proportions when they occupied the same ecological niche. Keywords: Lolium multiflorum, EPSPs, ALS, competition. RESUMO - O azevém é planta daninha importante nos cultivos de trigo devido à evolução da resistência a diferentes mecanismos de ação. O objetivo deste estudo foi comparar o desenvolvimento fenológico, custo adaptativo e habilidade competitiva entre biótipos de azevém suscetível e com resistência múltipla aos herbicidas inibidores da 5-enolpiruvilchiquimato-3-fosfato sintase (EPSPs) e acetolactato sintase (ALS). Para avaliar o custo adaptativo e o desenvolvimento fenológico, os biótipos foram cultivados em vasos, e as variáveis morfológicas de crescimento foram avaliadas até os 140 dias após a emergência. O desenvolvimento fenológico foi avaliado juntamente com o custo adaptativo. A habilidade competitiva foi determinada em experimento de série de substituição com proporções de azevém resistente e suscetível. As proporções testadas foram: 100:0 (estande puro de azevém resistente), 75:25, 50:50, 25:75 e 0:100% (estande puro de suscetível), onde o número de afilhos, a estatura, área foliar e massa seca da parte aérea foram avaliados aos 50 dias após a emergência. O maior período de afilhamento do azevém resistente é o principal fator envolvido na diferença do desenvolvimento fenológico entre os biótipos. O biótipo resistente é superior ao suscetível quanto a estatura (EP), massa seca da parte aérea (MSPA) e taxa de crescimento absoluto (TCA), enquanto o suscetível possui maior número de afilhos (NA) e razão de área foliar (RAF). Assim, o biótipo resistente não apresenta custo adaptativo. Para a habilidade competitiva, verificou-se que não há diferença entre os biótipos nas diferentes proporções testadas quando ocupam o mesmo nicho ecológico. Palavras-chave: Lolium multiflorum, EPSPs, ALS, competição